Finite Element Analysis Of Polydimethylsiloxane (Pdms) Strain Sensor For The Spinal Fusion Monitoring - Ng, Han We (Universiti Sains Malaysia, 2021)
In this project, Finite Element Simulation of PDMS capacitive bending strain sensor is conducted in order to observe the sensor performance in application of spinal fusion monitoring from the aspect of the sensitivity and nominal capacitance. The sensor design and dimension is originated from the sensor design (Mokti et al., 2011). In this project, dielectric material is manipulated to Polydimethylsiloxane (PDMS) to observe the change in sensor performance output. The simulated result is then compared to the result of design (Mokti et al., 2011) and verified by the calculation result. The current methods using a radiographic image do not reflect the fused spine progression accurately and therefore alternative methods are highly desired. Capacitive strain sensor is desired due to its low power consumption. This is because there is no DC current flow through the sensor element. Dielectric material used in this sensor model is PDMS that is suitable to be implanted in the human spinal bone because of its material properties of biocompatible, chemically inert and non-toxic. Besides, it is always been utilised to fabricate sensor due to its lower young modulus. This is a benefit to reduce the complexity level of fabrication process. QuickField Student 6.5 is the Finite Element Analysis (FEA) software used in this project to simulate the sensor capacitance output. There are three design parameters at which are the anchor length, anchor thickness and dielectric coverage in this project. Regarding to the simulated result, it was observed that the sensitivity is increased when anchor thickness and anchor length are increased. Among the three parameters, the dielectric coverage will result in highest capacitance output and sensitivity. The value of the sensitivity in the simulated result for 100%, 66% and 33% dielectric coverage are 0.1927pF/μɛ, 0.1607pF/μɛ and 0.1282pF/μɛ respectively at which are smaller than that in (Mokti et al., 2011) design model at which are 0.2513 pF/μɛ, 0.1906 pF/μɛ and 0.122 pF/μɛ respectively. Besides, the nominal capacitance of the three manipulated dielectric coverage in sensor is found higher in (Mokti et al., 2011) design model. This probably due to the dielectric constant of PDMS is slightly smaller than silicon dioxide.